Multilocus analysis of the catfish family Trichomycteridae (Teleostei: Ostariophysi: Siluriformes) supporting a monophyletic Trichomycterinae - Ochoa, Luz E. [UNESP]; Roxo, Fabio F. [UNESP]; DoNascimiento, Carlos; Sabaj, Mark H.; Datovo, Aléssio; Alfaro, Michael; Oliveira, Claudio [UNESP] (Elsevier, 2017)
Trichomycteridae is the second most diverse family of the order Siluriformes, its members are widely distributed through the freshwaters of Central and South America, exhibiting an exceptional ecological and phenotypic disparity. The most diverse subfamily, Trichomycterinae, represented mainly by the genus Trichomycterus, historically has been recognized as non-monophyletic and various characters used to unite or divide its constituents are repeatedly called into question. No comprehensive molecular phylogenetic hypothesis regarding relationships of trichomycterids has been produced, and the present study is the first extensive phylogeny for the family Trichomycteridae, based on a multilocus dataset of three mitochondrial loci and two nuclear markers (3284 bp total). Our analysis has the most comprehensive taxon-sampling of the Trichomycteridae published so far, including members of all subfamilies and a vast representation of Trichomycterus diversity. Analysis of these data showed a phylogenetic hypothesis with broad agreement between the Bayesian (BI) and maximum-likelihood (ML) trees. The results provided overwhelming support for the monophyletic status of Copionodontinae, Stegophilinae, Trichomycterinae, and Vandelliinae, but not Sarcoglanidinae and Glanapteryginae. A major feature of our results is the support to the current conceptualization of Trichomycterinae, which includes Ituglanis and Scleronema and excludes the “Trichomycterus” hasemani group. Divergence time analysis based on DNA substitution rates suggested a Lower Cretaceous origin of the family and the divergence events at subfamilial level shaped by Paleogene events in the geohistory of South America. This hypothesis lays a foundation for an array of future studies of evolution and biogeography of the family.
Keywords: Freshwater fishes; Molecular phylogeny; Neotropical region; Systematics